2011
DOI: 10.1124/jpet.111.179325
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib and 2,5-Dimethyl-Celecoxib Prevent Cardiac Remodeling Inhibiting Akt-Mediated Signal Transduction in an Inherited Dilated Cardiomyopathy Mouse Model

Abstract: Celecoxib, a cyclooxygenase-2 (COX-2)-selective nonsteroidal anti-inflammatory drug, has been shown to inhibit Akt and prevent cardiac remodeling in aortic banding-induced failing heart in mice. However, it may be difficult to use celecoxib for the treatment of heart failure because of thromboembolic adverse reactions. Since 2,5-dimethyl (DM)-celecoxib, a derivative unable to inhibit COX-2, has been also reported to inhibit Akt, we attempted to examine whether DM-celecoxib retains the ability to prevent cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…Moreover, randomized clinical trials have demonstrated that renal and cardiovascular safety of celecoxib has also become apparent, as well as its efficacy, tolerability, and safety in the elderly population . Growing evidence even indicated that celecoxib induces beneficial effects, rather than deleterious side effects, against cardiovascular stresses including inhibition of cardiac remodelling, cardiac fibrosis and cardiac inflammation . Therefore, in this study, we examined whether celecoxib could prevent pressure overload‐induced CH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, randomized clinical trials have demonstrated that renal and cardiovascular safety of celecoxib has also become apparent, as well as its efficacy, tolerability, and safety in the elderly population . Growing evidence even indicated that celecoxib induces beneficial effects, rather than deleterious side effects, against cardiovascular stresses including inhibition of cardiac remodelling, cardiac fibrosis and cardiac inflammation . Therefore, in this study, we examined whether celecoxib could prevent pressure overload‐induced CH.…”
Section: Discussionmentioning
confidence: 99%
“…Research recently confirmed that celecoxib can have therapeutic effects on the heart. Specifically, celecoxib prevented cardiac remodelling in mice with inherited dilated cardiomyopathy . Additionally, an in vitro study indicated that celecoxib not only was anti‐inflammatory in the vascular endothelium but it also reduced cardiac cell hypertrophy and fibrosis induced by angiotensin and aldosterone .…”
Section: Introductionmentioning
confidence: 97%
“…In our study, we could not revert Mcl-1 downregulation and DMC-induced apoptosis with the proteasome inhibitor MG132, thus suggesting a proteasome-independent effect. The ability of DMC and OSU-03012 to inhibit AKT activity (Wang et al, 2008;Fan et al, 2011) may give part of the answer. Indeed, PI3K/AKT pathway can prevent ER stress through an accumulation of GRP78 (Dai et al, 2010), and, on the other hand, AKT is also activated by GRP78 (Lin et al, 2011).…”
Section: Dmc Induces Apoptosis and Cell Cycle Alterations In Leukemiamentioning
confidence: 99%
“…Given the fact that COX-2 regulates the phosphorylation of GSK-3β (15), it is conceivable that COX-2 may play a role in GSK-3β signaling and in the regulation of mitochondrial function during hepatic I/R injury. Thus, we used flurbiprofen, a nonselective COX-1/COX-2 inhibitor, to further gain insight into the role of COX in mitochondrial function relevant to hepatic I/R injury.…”
Section: Introductionmentioning
confidence: 99%